PENGHAMBATAN CENDAWAN ENDOFIT ASAL TANAMAN KELOR UNTUK MENGENDALIKAN Colletotrichum sp. SECARA IN-VITRO - ASNIAH, ASNIAH; AMELIA, DEVI; SYAIR, SYAIR; TAUFIK, MUHAMMAD; HS, GUSNAWATY; SATRAH, VIT NERU; ULFA, NUR ISNAINI; BOTEK, MUHAMMAD (Jurnal Agroteknos, 2024)
Colletotrichum sp. is an important pathogen causing anthracnose in chili peppers. Anthracnose can cause yield losses of up to 90%. The control method commonly used by farmers is chemical control, but this method is not environmentally friendly. Endophytic fungi can be isolated from various plants, both cultivated plants and wild plants or weeds. Moringa is a plant that grows well in Southeast Sulawesi and is a vegetable that has excellent benefits due to its high nutritional content and potential as a biological agent. This study aimed to obtain endophytic fungi from moringa that have the potential to inhibit the growth of the pathogenic fungus Colletotrichum sp. in vitro. The research began with the exploration of endophytic fungi from moringa plant tissues. Subsequently, pathogenicity tests, inhibition tests using the dual culture method, and inhibition tests using the volatile compound method were conducted. The results showed that there were 3 (three) isolates of endophytic fungi from moringa that have potential as biological control agents for Colletotrichum sp., namely isolates ED02, EB01, and EB02. Isolate ED02 was the best biological agent for controlling Colletotrichum sp. in vitro, with dual culture inhibition and volatile compound inhibition percentages of 74.10% and 37.45%.